Outras leituras da tv brasileira: uma experiência com alunos das séries finais do ensino fundamental - Luciola Zacarias Mendes (2015)
The objective of this research is to analyze the perceptions of students in a class of 8th grade of elementary school of a public school of Belo Horizonte City television news about the Cidade Alerta and Malhação novel before and after conducting an educational project aimed at developing a reading more reflective and critical of these television programs. The pedagogical project relied mainly on the concepts of reading and education critical Freire (1983, 1996), in studies of literacies of Kleiman (2008) and Rojo (2012, 2013) and studies who think the relationship between media and education performed by Napolitano (2003) and Setton (2010). To start the search, students answered a questionnaire that revealed what image they have about these programs and what knowledge they had about the television media. In the subsequent step, the education project was developed. In it, besides the analysis of these programs, it was necessary to reflect on some aspects of the series Todo Mundo Odeia o Cris, and were produced short films, which sought to reflect the reinterpretation built in class. In the final step, the initial questionnaire was reapplied in order to verify the extent to which students have expanded the information we had on the television and there was a change in the way we perceive the studied programs. The data generated in this study, consisting of the questionnaires, the recording and the short films produced by students showed the importance of teacher-mediator in the knowledge construction process and the need to facilitate discussions aimed at a more critical reading of television content.